A recent review on Nanoemulsion as a topical delivery system of antipsoriatic drugs - Nimase, S.A.; Patil, P.B.; Saudagar, R.B. (Journal of Drug Delivery and Therapeutics, 2019)
Psoriasis and psoriatic arthritis are a chronic skin disease of autoimmune system that is identified as patches of abnormal skin, affecting 2-5% of the world’s population. Psoriasis is an incurable lifetime disease which can be controlled and relieved through medication. Various approaches have been explored to treat the disease. Treatment of psoriasis includes topical therapy, systemic therapy and phototherapy. Topical therapy is the main psoriasis treatment. However, the conventional topical treatment such as gel and cream have low efficiency to  poor cosmetic and aesthetic appeal leading to poor patient compliance or adherence. Nanoemulsions are transparent or translucent dispersions, having the droplet size less than 100 nm with ultra-low interfacial tension, large o/w interfacial areas and long term physical stability recently, much attention has been paid to the application of Nano emulsion as drug delivery system. A small droplet size would enhance the drug delivery and penetration of a drug through the psoriasis skin layer. A good selection of oils and surfactants would enhance the transdermal treatment efficacy in psoriatic patient.Keywords: Nano emulsion topical drug delivery, psoriatic treatment